PENGARUH IMPLEMENTASI PROGRAM KELUARGA HARAPAN TERHADAP KESEJAHTERAAN MASYARAKAT DI KELURAHAN KINILOW KECAMATAN TOMOHON UTARA KOTA TOMOHON - SITORUS, GABRIELLA KRISTIANY; RARES, JOYCE; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2020)
This research is motivated by the most prominent problem in Indonesia, namely poverty. One way that the Indonesian government has done to reduce the problem of poverty is to provide assistance to the poor, commonly referred to as social assistance or social assistance. Social Assistance is a transfer of money or goods given to the community to protect against the possibility of social risks and to improve the welfare of the community. To minimize the problems of social welfare, especially poverty, the Government of Indonesia has various prevention programs, one of which is a social assistance based program, the Family Hope Program (PKH). Tomohon City is one of the cities in Indonesia that was targeted by the program. The method used in this research is quantitative method. While the instruments and data collection techniques are interviews and questionnaires. Then, the analysis technique used is simple linear regression analysis to test the effect between variables. Based on research carried out and continued by analyzing the data obtained, that the implementation of the family hope program has an influence on the welfare of the community in Kinilow Village, Tomohon Utara District, Tomohon City. Keywords: Program Implementation, Community Welfare